The Use of Emerging Technologies for the Preservation and Dissemination of Islamic Traditions - Rizkitama, Gebie Yoga Efrizal; Muttaqin, Mohammad Izdiyan; Nurwahidin, Nurwahidin; Zainal, Veithzal Rivai (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
In the digital era, the preservation and dissemination of Islamic traditions face both disruption and opportunity due to the rapid proliferation of emerging technologies. This study aims to systematically identify how technologies such as artificial intelligence (AI), augmented and virtual reality (AR/VR), blockchain, and social media have been applied to support Islamic education, cultural heritage preservation, and religious communication. Using the PRISMA 2020 framework, a systematic literature review was conducted on 26 peer-reviewed studies published between 2020 and 2025 across Scopus, Google Scholar, ScienceDirect, and Taylor & Francis databases. The findings reveal diverse technological applications, from AI-based Qur'anic interpretation tools and VR-based ritual simulations to blockchain-driven manuscript authentication. These technologies contribute to educational innovation, cultural preservation, and digital da’wah while raising concerns over theological authenticity, spiritual commodification, and ethical alignment with Islamic values. The study concludes that emerging technologies offer meaningful pathways and cautionary implications for sustaining Islamic traditions in the digital age. Strategic engagement and ethical integration are crucial to ensuring that technological innovation reinforces rather than dilutes Islam's spiritual, cultural, and communal dimensions.